Smart home applications based on internet of things: Current scenario, issues and proposed solutions - Bakhit, Abdelmoneim Ahmed; Mohd Faizal, Jamlos; Alhaj, Nura Abdalrhman; Rizalman, Mamat; Hamza, Jamilu B. (Institute of Electrical and Electronics Engineers Inc., 2022)
The increasing deployment of the Internet of Things (IoT) across the globe has brought several issues in smart home applications to the forefront: the energy consumption of running these applications inside Home Area Networks (HAN) and the hungry bandwidth devices associated with the home appliance. Also, most of the recent growth in wireless network technologies makes it difficult to develop a standardization model to deploy IoT-related applications such as smart home applications. Several proposed solutions tackle the challenges associated with smart home applications, such as using low-power consumption wireless technologies like Zigbee. This article presents an overview of the state-of-the-art in the design, deployment, and challenges related to smart home IoT applications. The article also provides future recommendations for effective implementations of smart home applications.